KLASIFIKASI KEMANCETAN LALU LINTAS DI INDONESIA MENGGUNAKAN METODE NAIVE BAYES CLASSIFICATION - Alma Safira (Ridwan Institute, 2021)
This study discusses the protection of the law in it conducting the eradication of bankrupt property. The type of research that this research is normative. By using the sources - data sources of books literature and legislation that applies. In this study, the method of data analysis method qualitatively with data which is then processed into the results of research. The results of the study can be concluded that the duties and responsibilities of curators in the eradication of bankrupt property are very heavy. Curators are often districts or reporting both criminal and civil in their wrongdoing. This suggests that the protection of the curatorial profession is still lacking and there is no clear hukuum to protect the curator